L-Band Erbium-Doped Fiber Optimization and Transmission Investigation - Kaihua Hu; Li Pei; Jianshuai Wang; Zhouyi Hu; Wenxuan Xu; Long Zhang; Jing Li; Li Zhong (Photonics)
The optical spectrum resource in the C-band has been used up due to dense wavelength division multiplexing (DWDM). Because of devices’ compatibility with both the C-band and the L-band, the L-band is a good choice for further capacity expansion. Meanwhile, the mode division multiplexing (MDM) method has been applied to increase the number of channels. However, the few-mode erbium-doped fiber amplifier must be redesigned to overcome the power differences among channels. In this work, a few-mode erbium-doped fiber (FM-EDF) is optimized and manufactured. Then, an in-line gain-equalized L-band FM-EDFA is constructed. The experimental results show that the FM-EDFA works well in the wavelength range between 1575 nm and 1610 nm. The minimum differential modal gain (DMG) is 0.54 dB, and the maximum modal gain is 22.22 dB. Due to the excellent performance of the L-band FM-EDFA, a DSP-free transmission scheme in the L-band is demonstrated. The bit error rates (BERs) of each channel are below 1 × 10−5 with a DSP-free receiver.